Peran Ayah sebagai Orang Tua Tunggal dalam Pengasuhan Anak di Bawah Umur Pasca-Perceraian: Kajian Maqāṣid al-Syarī‘ah - Bela Meydarista; Eka Ramalia; Dilla Septiani; Nengsih Ari Saputri; Andini salsabila; Sri Mulyani (Journal of Sharia and Legal Science, 2025)
The increasing divorce rate has significantly changed family structures, resulting in children being raised by single parents, including fathers as sole caregivers. This study aims to examine the parenting patterns of single fathers towards minors after divorce, using an analytical framework based on the Maqāṣid al-Sharī‘ah. This study adopted an empirical qualitative approach, using primary data obtained through interviews and observations, as well as secondary data obtained from relevant literature and official documents. The findings indicate that single fathers' parenting practices primarily focus on meeting the child's basic physical, emotional, and spiritual needs. These practices are further analyzed in relation to the five main objectives of Maqāṣid al-Sharī‘ah (al-ḍarūriyyāt al-khamsah), namely ḥifẓ al-dīn (protection of religion), ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of reason), ḥifẓ al-nasl (protection of offspring), and ḥifẓ al-māl (protection of property). This study shows that the parenting patterns adopted by single fathers implicitly contribute to the realization of child welfare (maṣlaḥah), thus reflecting the substantive objectives of Islamic law as outlined in the framework of Maqāṣid al-Sharī‘ah.